PREGNACY RISK FACTORS FOR MAXILAR LABIAL AND PALAZAL FISSURES - Sotomayor Camayo, Justiniano (2004)
The possible etiologycal causes of cleft lip or palatine fissure occurrence are varied although there is nothing established definitively. At present time, it is believed that there is a hereditary genetic factor showed by the affectation of a member in the family. Other environmental factors contribute to produce fusion anomalies. The environmental factors contribute in critical time of lip and palate fusion. The aim of this investigation is to evaluate retrospectively “possible causes”, of oral fissures appearance. Thus, they will allow establish some predisposition factors. It was taken a patients sample with some type of oral fissure and their respective biological mother to evaluate retrospectively pregnant conditions (in the first trimester). It was stated as hypothesis that: “The predisposition factors happened during the first trimester of the pregnancy are the probable causes of the cleft lip or palatine fissures”. A sample of 108 patients having some type of oral fissure was used. They were surgically assisted in the Hogar Clínica San Juan de Dios (HCVD, Lima) during 1998 January-November period. It was determined diagnosis and type of oral fissure with their respective classification, family antecedent of fissure, maternal age and fratria (as genetic factors). Infection antecedents, medication exposure and radiation exposure during first trimester pregnancy (as environmental factors) ;and the mother's knowledge statement on possible cause of their children fissure.